Optimizing Nurse Staffing: The Impact of Nurse-to-Patient Ratios and Empowerment on Patient Satisfaction in Riyadh Health Clusters - Aladhyani, Saleh Ishq; Ali, Dhakir Abbas; Said, Faridah Mohd; Almotairi, Salah (Inspirasi Foundation, 2025)
Introduction: Saudi Arabia’s Vision 2030 has transformed healthcare delivery through the Riyadh Health Clusters, integrating hospitals and primary care centers to improve efficiency and patient outcomes. Within this context, nurse-to-patient ratios and employee empowerment have emerged as critical factors influencing patient satisfaction but remain underexplored in the Saudi healthcare system. Objective: This study examines the impact of nurse-to-patient ratios and employee empowerment on patient satisfaction within Riyadh Health Clusters, a transformative healthcare model under Saudi Arabia’s Vision 2030. Methods: Using a quantitative, cross-sectional design, data were collected from 384 healthcare professionals, predominantly nurses, across three clusters. Results: Linear regression analyses revealed a statistically significant but modest positive relationship between nurse-to-patient ratios and employee empowerment (β = 0.18, R² = 0.04, p < 0.05), underscoring the limited explanatory role of staffing adequacy in isolation. In contrast, employee empowerment demonstrated a robust impact on patient satisfaction (β = 0.45, R² = 0.56, p < 0.001), highlighting its centrality to care quality. The findings align with Kanter’s Structural Empowerment Theory but diverge from Western models due to Riyadh’s unique challenges, including hierarchical organizational cultures, a predominantly expatriate nursing workforce (70%), and urban-rural resource disparities. Conclusion: The study emphasizes the need for context-specific strategies that integrate staffing reforms with empowerment initiatives, such as leadership training and participatory decision-making, to mitigate workforce burnout and standardize care practices. These insights advance global healthcare literature by contextualizing empowerment dynamics in non-Western settings and offer actionable recommendations for policymakers to align Riyadh’s cluster model with Vision 2030’s patient-centered goals.